Woodland and forest - Ambrose, Jamie (Author of nature books for children); Burnie, David; Gamlin, Linda (New York, New York DK Publishing, 2017)
Examines different types of forests, and looks at the types of plants and animals that call them home.--
"Explore nature with fun facts and activities"--Cover
Includes index
science (Nature )
1
Keywords: Forest animals -- Juvenile literature; Forest animals; Forest ecology -- Juvenile literature; Forest ecology; Forests and forestry -- Juvenile literature; Forests and forestry; Forest animals; Forest ecology; Forests and forestry; Juvenile works